Upstream regulation for initiation of restricted Shh expression in the chick limb bud. Issue 5 (16th March 2017) - Matsubara, Haruka; Saito, Daisuke; Abe, Gembu; Yokoyama, Hitoshi; Suzuki, Takayuki; Tamura, Koji
Abstract : Background : The organizing center, which serves as a morphogen source, has crucial functions in morphogenesis in animal development. The center is necessarily located in a certain restricted area in the morphogenetic field, and there are several ways in which an organizing center can be restricted. The organizing center for limb morphogenesis, the ZPA (zone of polarizing activity), specifically expresses the Shh gene and is restricted to the posterior region of the developing limb bud.Results : The pre‐pattern along the limb anteroposterior axis, provided by anterior Gli3 expression and posterior Hand2 expression, seems insufficient for the initiation of Shh expression restricted to a narrow, small spot in the posterior limb field. Comparison of the spatiotemporal patterns of gene expression between Shh and some candidate genes ( Fgf8, Hoxd10, Hoxd11, Tbx2, and Alx4 ) upstream of Shh expression suggested that a combination of these genes' expression provides the restricted initiation of Shh expression.Conclusions : Taken together with results of functional assays, we propose a model in which positive and negative transcriptional regulatory networks accumulate their functions in the intersection area of their expression regions to provide a restricted spot for the ZPA, the source of morphogen, Shh. Developmental Dynamics 246:417–430, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Sonic hedgehog, transcriptional regulation, limb development.